Equal palliative care for patients with COPD? A nationwide register study. (3rd April 2019) - Henoch, Ingela; Strang, Peter; Löfdahl, Claes-Göran; Ekberg-Jansson, Ann
Abstract: Background: Although chronic obstructive pulmonary disease (COPD) is a life-limiting disease with a significant symptom burden, the patients are more often referred to nursing homes (NH), than to specialist palliative care (SPC) at the end of life (EOL). This study aimed to compare patients with COPD in SPC with those in NH and to compare the care provided. Methods: A national register study was carried out where the Swedish National Airway Register and the Swedish Register of Palliative Care were merged. COPD patients who died in NHs or short-term facilities were included in the NH group ( n = 415) and those who died in SPC were included in the SPC group ( n = 355). Demographic and clinical variables were included from the Swedish National Airway Register and variables concerning EOL care from the Swedish Register of Palliative Care. Results: Symptom prevalence was similar in NHs and SPC, but symptom assessment (32% vs 20%), symptom relief medication (93-98% in SPC vs 74-90% in NH), EOL discussions (88% vs 66%), and bereavement support (94% vs 67%) were more likely in SPC (in all comparisons p < 0.001). Younger age and co-habiting increased the probability of dying in SPC ( p < 0.001). Conclusion: Despite similar symptom prevalence, older persons are more likely to be referred to NHs. If applying a palliative care philosophy in NHs, routine symptom assessment and prescription of rescue medication for frequent symptoms, would be more likely. Promoting advance care planning and EOL discussions at an earlier stage would result in more prepared patients and families.